MUSEUM BENTENG VREDEBURG SEBAGAI SUMBER PEMBELAJARAN SEJARAH - Kustyaningsih, Ayiek; Djono, Djono; Yuniyanto, Tri (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2018)
The purpose of this research is describe the types of the Vredeburg Fort Museum?s collection which can be applied as the source of History Learning material in SMA Negeri 10 Yogyakarta which is implemented in history learning and knowing obstacles of history learning in SMA Negeri 10 Yogyakarta. This research is a descriptive qualitative research, which is a technique to analyze phenomena by creating descriptive data. The data source that used were place, event, informant, and document. The techniques of collecting data used in the research were observation, interview, and document analysis. The sampling technique used was purposive sampling. Data validation techniques that used were source and method triangulation. The cata were analyzed by using interactive analysis technique which is a technique of analysis combining three components, such as data reduction, data presentation and drawing conclusion.Based on the result of the research, it can be concluded that (1) Historical things can be integrated in the learning process. It is because those things are related to historical events in the past. This can strengthen student?s ability in remembering Historical events, (2) the use of Museum as the source of History learning material in SMA Negeri 10 Yogyakarta had some alternatives in the implementation. If it is necessary, the teacher may invite the students to visit the museum. If it is not, the teacher still has another media to be taught to the students, (3) the implementation divided into several stages. The teacher used discussion and homework in the learning process. This is because the methods have an advantages in terms of learning time allocation, and (4) The teacher had no obstacles in choosing a learning method so far. If this happens in the future, the role of the teacher is very important.